Pole piece, preparation method and battery

By adopting a layered design and protective layer on the electrodes of the lithium-ion battery, the risk of thermal runaway of the ternary positive electrode materials is solved, the high energy density and safety of the battery are balanced, and the chemical stability and flame retardant performance of the battery are improved.

CN120565573APending Publication Date: 2025-08-29JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510502630.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the high energy density of the ternary positive electrode material is accompanied by high heat release and thermal runaway risk, resulting in safety problems, especially in the fast charging process, which is prone to fire.

Method used

Using a layered electrode sheet structure, the first active material layer, the second active material layer and the protective layer are sequentially coated on the current collector. The protective layer consists of silicone rubber and additives, including flame retardant, reinforcement and vulcanizing agent, to enhance the chemical stability and flame retardant properties of the battery.

Benefits of technology

Effectively reduce the risk of thermal runaway from the battery, improve the stability and flame retardant performance of the battery, and improve the flexibility and circulation performance of the pole plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005369093450000171
    Figure BDA0005369093450000171
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a pole piece, a preparation method and a battery. The disclosed pole piece comprises a current collector, a first active material layer, a second active material layer and a protective layer, the first active material layer is arranged on at least one surface of the current collector, and the first active material layer comprises a first active material; the second active material layer is arranged on the surface, far away from the current collector, of the first active material layer, and the second active material layer comprises a second active material; the protective layer is arranged on the surface, away from the first active material layer, of the second active material layer and comprises silicone rubber and an additive. The risk of thermal runaway of the battery can be effectively reduced, and the stability and flame retardance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a pole piece, a preparation method and a battery. Background Art

[0002] As a key technology for new energy vehicles, lithium-ion batteries are crucial for their performance and safety. With increasing demands for battery energy density and operating environments, high-energy-density ternary cathode materials are becoming widely used. However, these materials release far more heat and pose a much higher risk of thermal runaway than other battery systems.

[0003] In view of this, it is crucial to obtain an electrode with electrochemical stability and flame retardancy to enhance the cycle performance and safety performance of the battery. Summary of the Invention

[0004] In view of this, the present invention aims to at least partially address one of the technical problems in the related art. The present invention provides a pole piece, a preparation method, and a battery that can effectively reduce the risk of thermal runaway of the battery and improve the stability and flame retardancy of the battery.

[0005] According to a first aspect of the present invention, the present invention provides a pole piece, comprising:

[0006] current collector;

[0007] a first active material layer, the first active material layer being disposed on at least one surface of the current collector, the first active material layer comprising a first active material;

[0008] a second active material layer, the second active material layer being disposed on a surface of the first active material layer away from the current collector, the second active material layer comprising a second active material;

[0009] A protective layer is provided on a surface of the second active material layer away from the first active material layer, and the protective layer comprises silicone rubber and additives.

[0010] In an optional embodiment, the protective layer includes the following components in parts by mass: 100 parts of silicone rubber and 86.5 to 97 parts of additives.

[0011] In an optional embodiment, the additives include a flame retardant, a reinforcing agent and a vulcanizing agent, and the masses of the flame retardant, the reinforcing agent and the vulcanizing agent are not zero.

[0012] In an optional embodiment, the protective layer includes the following components in parts by mass: 100 parts of silicone rubber, 45-50 parts of reinforcing agent, 40-45 parts of flame retardant and 1.5-2 parts of vulcanizing agent.

[0013] In an optional embodiment, the protective layer satisfies at least one of features (1) to (3): (1) the flame retardant includes at least one of aluminum hydroxide or magnesium hydroxide; (2) the reinforcing agent includes fumed silica; (3) the vulcanizing agent includes di-tetra-sulfurized agent.

[0014] In an optional embodiment, the first active material and the second active material are positive electrode active materials.

[0015] In an optional embodiment, the positive electrode active material includes at least one of a ternary material, lithium iron phosphate, or lithium manganese iron phosphate.

[0016] In an optional embodiment, the first active material includes a ternary material A; preferably, the ternary material A includes LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein, x≥0.8, 0.05≤y≤0.2.

[0017] In an optional embodiment, the ternary material A includes primary particles;

[0018] In an optional embodiment, the second active material includes a ternary material B; preferably, the ternary material B includes LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein, x≥0.8, 0.05≤y≤0.2.

[0019] In an optional embodiment, the ternary material B includes secondary particles.

[0020] In an optional embodiment, both the first active material and the second active material contain nickel, and the nickel content in the first active material is different from the nickel content in the second active material.

[0021] In an optional embodiment, the first active material and the second active material are negative electrode active materials.

[0022] In an optional embodiment, the first active material includes at least one of a silicon-based material and a carbon-based material; the first active material includes primary particles; the second active material includes at least one of a silicon-based material and a carbon-based material; and the second active material includes secondary particles.

[0023] In an optional implementation manner, the thickness of the protective layer is 3 μm to 10 μm.

[0024] In an optional embodiment, the surface density of the protective layer is 15 mg / m 2 ~30 mg / m 2 .

[0025] In an optional embodiment, based on the mass of the first active material layer, the mass of the first active material accounts for 95% to 97%.

[0026] In an optional embodiment, the first active material layer further includes a first conductive agent and a first binder.

[0027] In an optional embodiment, based on the mass of the first active material layer, the mass of the first conductive agent accounts for 1% to 1.5%.

[0028] In an optional embodiment, based on the mass of the first active material layer, the mass of the first binder accounts for 2% to 3.5%.

[0029] In an optional embodiment, the first conductive agent includes one or more of conductive carbon black, vapor-generated carbon fibers, graphene, or carbon nanotubes.

[0030] In an optional embodiment, based on the mass of the second active material layer, the mass of the second active material accounts for 95% to 97%.

[0031] In an optional embodiment, the second active material layer further includes a second conductive agent and a second binder.

[0032] In an optional embodiment, based on the mass of the second active material layer, the mass of the second conductive agent accounts for 1% to 1.5%.

[0033] In an optional embodiment, based on the mass of the second active material layer, the mass of the second binder accounts for 2% to 3.5%.

[0034] In an optional embodiment, the second conductive agent includes one or more of conductive carbon black, vapor-generated carbon fibers, graphene, or carbon nanotubes.

[0035] According to a second aspect of the present invention, the present invention provides a method for preparing a pole piece, comprising the following steps:

[0036] Coating a first slurry on at least one side of the current collector to obtain a first active material layer;

[0037] coating a second slurry on the surface of the first active material layer to obtain a second active material layer;

[0038] coating a protective slurry on the surface of the second active material layer to obtain a protective layer;

[0039] The first active material layer includes a first active material; the second active material layer includes a second active material; and the protective layer includes silicone rubber and additives.

[0040] In an optional embodiment, the step of obtaining the protective layer specifically includes:

[0041] The silicone rubber and the additive are mixed evenly to obtain a protective slurry; preferably, the silicone rubber, the flame retardant, the reinforcing agent and the vulcanizing agent are mixed evenly to obtain a protective slurry;

[0042] The protective slurry is coated on the surface of the second active material layer with a doctor blade having a coating thickness of 10 μm to 40 μm. After drying, the protective layer is obtained.

[0043] According to a third aspect of the present invention, the present invention further provides a battery, comprising: a separator, an electrolyte, and the pole piece according to any embodiment of the first aspect of the present invention.

[0044] In an optional embodiment, the battery further comprises a pole piece produced by the preparation method described in any embodiment of the second aspect of the present invention.

[0045] The electrode, preparation method, and battery provided by the present invention also have the following beneficial effects:

[0046] In an embodiment of the present invention, a pole piece is provided in which a first active material layer, a second active material layer and a protective layer are arranged on the current collector, and the protective layer includes silicone rubber and additives. By providing a protective layer containing silicone rubber, the risk of thermal runaway of the battery can be effectively reduced, and the chemical stability and thermal stability of the battery can be improved, thereby improving the cycle performance and safety performance of the battery. At the same time, the protective layer also has a high tensile strength, which can improve the flexibility of the pole piece.

[0047] Additional aspects and advantages of the present invention will be set forth in part in the description which follows and, in part, will be obvious from the description which follows, or may be learned by practice of the present invention. DETAILED DESCRIPTION

[0048] The present invention will be further described below with reference to specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention.

[0049] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.

[0050] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.

[0051] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0052] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0053] Unless otherwise specified, the terms "include" and "comprising" used in the present invention may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0054] Ternary materials are often used to increase the energy density of lithium-ion batteries. However, the high energy density of ternary materials comes with higher safety risks associated with lithium-ion batteries. For example, the high heat released by ternary materials increases the risk of thermal runaway, making the battery more susceptible to fire and other problems.

[0055] In view of the above-mentioned problems, the present invention provides a pole piece, a preparation method and a battery, which can effectively reduce the risk of thermal runaway of the battery and improve the stability and flame retardancy of the battery.

[0056] The technical solutions provided by the present invention are as follows:

[0057] [Pole piece]

[0058] In some embodiments, a pole piece is provided, which includes: a current collector, a first active material layer and a second active material layer; the first active material layer is arranged on at least one surface of the current collector, and the first active material layer includes a first active material; the second active material layer is arranged on the surface of the first active material layer away from the current collector, and the second active material layer includes a second active material.

[0059] In the present application, the current collector includes but is not limited to any one of a homogeneous aluminum foil, a porous aluminum foil, an aluminum foil with a carbon coating layer, a copper foil or an aluminum alloy foil. In the thickness direction, a first active material layer is provided on a single surface or a double surface of the current collector, and a second active material layer is provided on the first active material layer. As an example, the current collector has two surfaces opposite to each other in its own thickness direction, the first active material layer is provided on the two opposite surfaces of the current collector, and the second active material layer is further provided on the surface of the first active material layer. It is understood that in other embodiments, the first active material layer can also be formed on either of the two surfaces of the current collector. The "surface" here can be the entire area of ​​the current collector or a partial area of ​​the current collector. This application has no special restrictions on this, as long as the purpose of this application can be achieved.

[0060] In an embodiment of the present invention, a pole piece can be used in a battery cell structure. Specifically, the pole piece can be a positive pole piece or a negative pole piece. That is, the polarity of the pole piece can be positive or negative. In particular, based on the existing demand for improved fast charging and energy density of positive pole pieces, as well as the requirements for chemical stability and thermal stability, this pole piece is more preferred as a positive pole piece.

[0061] For example, in some embodiments, the electrode is a positive electrode. When the electrode is a positive electrode, the first active material layer and the second active material layer both include positive electrode active materials.

[0062] As an example, the first active material layer includes a first active material, and the second active material layer includes a second active material; the first active material and the second active material may include but are not limited to ternary materials, lithium iron phosphate or lithium iron manganese phosphate and other positive electrode active materials. For example, the first active material can be selected from a ternary material with high energy density, such as NCM (LiNi x Co y Mn x O2) or NCA(LiNi x Co y Al z O2) one or more, specifically NCM811 or NCM532; the second active material can be selected from one or more of NCM811, NCM532 or NCA.

[0063] The first and second active materials can differ in their crystal structures, particle sizes, nickel content, or cobalt content. For example, the first and second active materials have different crystal structures, with the first active material being a single crystal and the second being a polycrystalline material. This can enhance the structural stability of the electrode. Because the first active material is a single crystal, the absence of internal grain boundaries allows for improved structural stability, reducing the generation of microcracks during charge and discharge, thereby improving cycling stability. Furthermore, because the first active material is located in the first active material layer close to the current collector, the single crystal first active material provides better thermal stability in the lower layer, reducing the risk of thermal runaway. The polycrystalline second active material, located in the second active material layer further from the current collector, provides better electrochemical activity. Furthermore, a first active material layer made of a single crystal can reduce side reactions with the electrolyte, improving battery safety and lifespan.

[0064] For example, the first active material in the first active material layer near the current collector is a polycrystalline material, while the second active material in the second active material layer farther from the current collector is a single crystal material. Polycrystalline materials generally have higher electrical conductivity, and placing them in the bottom layer can improve the conductivity of the entire electrode, thereby enhancing the battery's rate performance. Furthermore, placing the polycrystalline material in the bottom layer helps reduce battery polarization, increase the rate discharge median voltage, and reduce side reactions during battery storage. Due to their higher electrical conductivity and larger specific surface area, polycrystalline materials can improve the battery's rate performance.

[0065] Of course, the materials in the first active material and the second active material can have different nickel content. By superimposing the nickel content in the two active material layers, a synergistic gain effect can be achieved, further improving the capacity of the battery.

[0066] In some embodiments, the pole piece further includes a protective layer, which is disposed on a surface of the second active material layer away from the first active material layer, and includes silicone rubber and additives.

[0067] To prevent the risk of thermal runaway during fast charging and other processes, a protective layer is provided on the surface of the second active material layer, forming a pole piece structured sequentially as a current collector, a first active material layer, a second active material layer, and a protective layer. That is, the pole piece includes a current collector, a first active material layer, a second active material layer, and a protective layer stacked in sequence.

[0068] The protective layer includes silicone rubber. The raw rubber of the silicone rubber can be one or more of methyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, or fluorosilicone rubber. The raw rubber is cross-linked with a vulcanizing agent to form the silicone rubber. To further enhance the cross-linking of the silicone rubber, additives such as white carbon black and aluminum oxide can be added to the raw rubber to significantly enhance the high-temperature resistance and mechanical properties of the silicone rubber.

[0069] By setting up this protective layer, the battery can be guaranteed to have high energy density while also having excellent safety performance. The protective layer can improve the high temperature resistance of the electrode and avoid the risk of thermal runaway, fire, etc. due to sudden generation of high heat in the battery. The protective layer containing silicone rubber can also improve the mechanical properties and cycle stability of the electrode to a certain extent.

[0070] Therefore, the electrode of the present application not only has the active material layer arranged in layers, but also has a protective layer. The layered design can take into account both energy density and dynamic performance; the protective layer is provided on the outermost side of the electrode to improve the chemical and thermal stability of the electrode, thereby improving the cycle performance and safety performance of the battery. At the same time, the first active material layer and the second active material layer have high tensile strength to improve the flexibility of the electrode. For example, if one of the first active material layer and the second active material layer is a single crystal layer and the other is a polycrystalline layer, the use of the single crystal layer can improve the cycle performance, and the use of the polycrystalline layer can improve the energy density.

[0071] In some embodiments, the protective layer includes the following components in parts by weight: 100 parts of silicone rubber and 86.5 to 97 parts of additives.

[0072] Specifically, the mass fraction of silicone rubber is 100 parts, and the mass fraction of the additive can be 86.5 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts or 97 parts; limiting the mass fraction range of silicone rubber and additives can improve the crosslinking degree of silicone rubber to a certain extent, thereby improving the mechanical properties of the protective layer, and enabling the electrode to have good flexibility and high temperature resistance.

[0073] In some embodiments, the additives include a flame retardant, a reinforcing agent and a vulcanizing agent, and the masses of the flame retardant, the reinforcing agent and the vulcanizing agent are not 0; preferably, the protective layer includes the following components in parts by mass: 100 parts of silicone rubber, 45-50 parts of reinforcing agent, 40-45 parts of flame retardant and 1.5-2 parts of vulcanizing agent.

[0074] Reinforcing agents include, but are not limited to, sepiolite, zinc oxide, magnesium oxide, or carbon black, with fumed silica being a preferred reinforcing agent. The weight percentage of the reinforcing agent can be 45, 46, 47, 48, 49, or 50 parts. Flame retardants include, but are not limited to, magnesium hydroxide, aluminum hydroxide, or ammonium phosphate, and the weight percentage of the flame retardant can be 45, 46, 47, 48, 49, or 50 parts. Vulcanizing agents include, but are not limited to, sulfur monochloride or sulfur, and the weight percentage of the vulcanizing agent can be 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0 parts. Flame retardants can impart flame retardancy to the protective layer, effectively preventing fires from occurring during thermal runaway. Reinforcing agents can effectively enhance the strength and high-temperature resistance of the protective layer, further enhancing the safety performance of the battery. Vulcanizing agents can form a complex three-dimensional network structure within the silicone rubber, enhancing the physical and mechanical properties of the silicone rubber.

[0075] In some preferred embodiments, the flame retardant in the protective layer includes at least one of aluminum hydroxide or magnesium hydroxide.

[0076] Aluminum hydroxide or magnesium hydroxide is used as a flame retardant. When the battery experiences thermal runaway, the temperature rises and aluminum hydroxide or magnesium hydroxide can decompose into oxides and water at high temperatures, reducing the temperature of the heating and combustion site. The generated water is converted into water vapor at high temperatures, which can isolate oxygen and have a flame retardant effect. At the same time, the decomposition temperature of magnesium hydroxide and aluminum hydroxide is low, which can make the protective layer more sensitive and play a flame retardant role in the early stage of thermal runaway, preventing the thermal runaway from spreading further. In addition, aluminum hydroxide has flame retardancy and may participate in the formation of a cross-linked network in silicone rubber, improving the heat resistance and chemical resistance of the protective layer.

[0077] In some preferred embodiments, the reinforcing agent in the protective layer includes fumed silica.

[0078] Fumed silica is chosen as a reinforcing agent due to its excellent dispersibility. When mixed with silicone rubber, it can be evenly dispersed. Furthermore, its large specific surface area and surface adsorption capacity can further enhance the strength of silicone rubber. The microporous structure of fumed silica helps to improve the physical strength and wear resistance of silicone rubber, further extending the service life of the protective layer.

[0079] In some preferred embodiments, the vulcanizing agent in the protective layer includes bis(di-tetra)sulfur.

[0080] During the vulcanization process of silicone rubber, di-tetra-vulcanizing agent can promote the cross-linking between the rubber molecules of silicone rubber, thereby improving the thermal stability, mechanical strength and aging resistance of the protective layer; and a good cross-linking network helps to maintain the structural integrity of the material.

[0081] In some preferred embodiments, the protective layer includes the following components in parts by mass: 100 parts of silicone rubber, 45-50 parts of fumed silica, 40-45 parts of aluminum hydroxide, and 1.5-2 parts of bis(di-tetra-)sulfurized agent.

[0082] By providing the above-mentioned protective layer, the electrode can have both electrochemical stability and flame retardancy, thereby enhancing the cycle performance and safety performance of the battery.

[0083] In some embodiments, the electrode is a positive electrode, and the first active substance and the second active substance are positive electrode active materials. When the electrode is a positive electrode, the protective layer may also be referred to as an artificial CEI film, which can provide the electrode with both electrochemical stability and flame retardancy, thereby enhancing the battery's cycling performance and safety.

[0084] If the electrode is a positive electrode, the positive electrode active material includes but is not limited to a ternary material, lithium iron phosphate or lithium iron manganese phosphate; the first active substance and the second active substance can be the same in the selection of positive electrode active materials, and preferably different ones can be selected, and a gradient is formed between the first active substance layer and the second active substance layer, which can improve the capacity and cycle rate of the battery.

[0085] In some embodiments, the first active material comprises a ternary material A; preferably, the ternary material A comprises LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein, x≥0.8, 0.05≤y≤0.2.

[0086] Ternary material A includes but is not limited to LiNi 0.8 Co 0.05 Mn 0.15 O2、LiNi 0.85 Co 0.05 Mn 0.15 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.92 Co 0.05 Mn 0.03 O2、LiNi 0.8 Co 0.05 Al 0.15 O2、LiNi 0.8 Co 0.2 O2、LiNi 0.9 Co 0.1 Al 0.1 O2 or LiNi 0.85 Co 0.05Al 0.1 Any one of O2 or any point value within the range of any one of x and y. Ternary material A is selected from ternary materials with high nickel content, which can ensure that the battery has high energy density and cycle performance.

[0087] In some embodiments, ternary material A includes primary particles;

[0088] By limiting the ternary material A to primary particles, the ternary material A has good structural stability, its grains will not break under high temperature conditions, and it has good cycle stability, thereby improving the safety performance of the battery.

[0089] In some embodiments, the second active material comprises a ternary material B; preferably, the ternary material B comprises LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein, x≥0.8, 0.05≤y≤0.2.

[0090] Ternary materials B include but are not limited to LiNi 0.8 Co 0.05 Mn 0.15 O2、LiNi 0.85 Co 0.05 Mn 0.15 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.92 Co 0.05 Mn 0.03 O2、LiNi 0.8 Co 0.05 Al 0.15 O2、LiNi 0.8 Co 0.2 O2、LiNi 0.9 Co 0.1 Al 0.1 O2 or LiNi 0.85 Co 0.05 Al 0.1 Any one of O2 or any point value within the range of any one of x and y. Ternary material B is selected from ternary materials with high nickel content, which can ensure that the battery has high energy density and cycle performance.

[0091] In some embodiments, ternary material B includes secondary particles.

[0092] By limiting the ternary material B to secondary particles, the second active material layer can have a high compaction density, thereby improving the energy density of the battery, and the second active material layer can have good mechanical strength and toughness. The particle grains of the ternary material B can be well controlled, and particle grading can be formed to improve the capacity and cycle performance of the battery.

[0093] Alternatively, in some embodiments, ternary material A comprises secondary particles and ternary material B comprises primary particles.

[0094] Ternary material A and ternary material B in this application preferably have different crystal structures or particle sizes. For example, ternary material A may comprise primary particles and ternary material B may comprise secondary particles; or ternary material A may comprise secondary particles and ternary material B may comprise primary particles. Alternatively, ternary material A may comprise a single crystal material and ternary material B may comprise a polycrystalline material; or ternary material A may comprise a polycrystalline material and ternary material B may comprise a single crystal material.

[0095] In some embodiments, both the first active material and the second active material contain nickel, and the nickel content in the first active material is different from the nickel content in the second active material.

[0096] By setting the nickel content in the first active material to be different from the nickel content in the second active material, the first active material layer and the second active material layer have a nickel content gradient, and the two active material layers work synergistically to improve the safety performance and capacity of the battery.

[0097] In some embodiments, the electrode is a negative electrode, and the first active material and the second active material are negative electrode active materials.

[0098] The electrode sheet of the present application can also be a negative electrode sheet, so the above-mentioned first active substance and second active substance can also be negative electrode active materials to prepare a negative electrode sheet; the negative electrode active material includes but is not limited to one or more of graphite, hard carbon, soft carbon, molybdenum trioxide or carbon nanotubes.

[0099] In some embodiments, the first active material includes at least one of a silicon-based material and a carbon-based material; the first active material includes primary particles; the second active material includes at least one of a silicon-based material and a carbon-based material; and the second active material includes secondary particles.

[0100] Alternatively, in some embodiments, the first active material includes secondary particles; and the second active material includes primary particles.

[0101] Artificial graphite, natural graphite or graphene in carbon-based materials, and silicon dioxide or molybdenum trioxide in silicon-based materials can all be used as the first active material and the second active material; at the same time, the first active material includes primary particles, and the second active material includes secondary particles. The first active material layer close to the current collector can have a more stable structure, and the second active material layer has a higher compaction density, thereby enabling the battery to have excellent safety performance and high energy density.

[0102] In some embodiments, the protective layer has a thickness of 3 μm to 10 μm.

[0103] Specifically, the thickness of the protective layer can be any one of 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, or 10μm, or any value in between. By limiting the thickness of the protective layer, safety performance can be better guaranteed while also ensuring that costs are not excessively high. If the thickness exceeds this range, waste will result and significantly increase costs. If it is too low, safety and flame retardancy will not be achieved.

[0104] In some embodiments, the surface density of the protective layer is 15 mg / m 2 ~30 mg / m 2 .

[0105] Specifically, the surface density of the protective layer can be 15 mg / m 2 , 16mg / m 2 , 17mg / m 2 , 18mg / m 2 , 19mg / m 2 , 20mg / m 2 , 24mg / m 2 , 26mg / m 2 or 30 mg / m 2 By limiting the surface density of the protective layer, it is possible to ensure that lithium ions can shuttle through the protective layer, thereby ensuring the battery's cycle rate performance. If the density is too high, it will hinder the shuttle of lithium ions and reduce the battery's rate performance, while if it is too low, it will not have any protective effect.

[0106] In some embodiments, based on the mass of the first active material layer, the mass of the first active material accounts for 95% to 97%.

[0107] The mass proportion of the first active material in the first active material layer can be any one of 95%, 96% or 97%. Optionally, the first active material layer can also include a binder to promote dense bonding of the first active material.

[0108] In some embodiments, the first active material layer further includes a first conductive agent and a first binder; preferably, based on the mass of the first active material layer, the mass proportion of the first conductive agent is 1% to 1.5%; preferably, based on the mass of the first active material layer, the mass proportion of the first binder is 2% to 3.5%.

[0109] As an example, the mass proportion of the first conductive agent can be any one of 1%, 1.2% or 1.5% or any point between any two of them; the mass proportion of the first adhesive can be any one of 2%, 2.5%, 3%, 3.2% or 3.5% or any point between any two of them.

[0110] The first conductive agent includes but is not limited to one or more of conductive carbon black, vapor-generated carbon fiber, graphene or carbon nanotubes; the first binder includes but is not limited to one or more of sodium carboxymethyl cellulose, polyvinylidene fluoride or styrene-butadiene rubber.

[0111] In some embodiments, based on the mass of the second active material layer, the mass of the second active material accounts for 95% to 97%.

[0112] The mass proportion of the second active material in the second active material layer can be any one of 95%, 96% or 97%. Optionally, the second active material layer can also include a binder to promote the dense bonding of the second active material.

[0113] In some embodiments, the second active material layer further includes a second conductive agent and a second binder; preferably, based on the mass of the second active material layer, the mass proportion of the second conductive agent is 1% to 1.5%; preferably, based on the mass of the second active material layer, the mass proportion of the second binder is 2% to 3.5%; preferably, the second conductive agent includes one or more of conductive carbon black, vapor-generated carbon fiber, graphene or carbon nanotubes.

[0114] The mass proportion of the second conductive agent can be any one of 1%, 1.2% or 1.5% or any point between any two of them; the mass proportion of the second adhesive can be any one of 2%, 2.5%, 3%, 3.2% or 3.5% or any point between any two of them.

[0115] The second conductive agent includes but is not limited to one or more of conductive carbon black, vapor-generated carbon fiber, graphene or carbon nanotubes; the second binder includes but is not limited to one or more of sodium carboxymethyl cellulose, polyvinylidene fluoride or styrene-butadiene rubber.

[0116] [Method for preparing electrode]

[0117] The present invention also provides a method for preparing a pole piece, comprising the following steps:

[0118] S101 , coating a first slurry on at least one surface of a current collector to obtain a first active material layer.

[0119] A first slurry is coated on one or both sides of the current collector to obtain a first active material layer, wherein the first slurry includes a first active material, a first binder, and a first conductive agent.

[0120] S102 , coating a second slurry on the surface of the first active material layer to obtain a second active material layer.

[0121] The second slurry includes a second active material, a second binder, and a second conductive agent. The obtained second slurry is coated on the first active material layer to obtain the second active material layer.

[0122] S103 , coating a protective slurry on the surface of the second active material layer to obtain a protective layer.

[0123] The protective slurry includes silicone rubber and additives, and the uniformly mixed protective slurry is coated on the second active material layer to obtain a protective layer.

[0124] In some embodiments, the step of obtaining the protective layer specifically includes:

[0125] S201, uniformly mix the silicone rubber and additives to obtain a protective slurry; preferably, uniformly mix the silicone rubber, flame retardant, reinforcing agent and vulcanizing agent to obtain a protective slurry.

[0126] Silicone rubber, flame retardant, reinforcing agent and vulcanizing agent are added to an internal mixer or an open mixer for mixing. It will be understood by those skilled in the art that the temperature and time for mixing using an open mixer or an internal mixer can be selected by those skilled in the art based on the present invention and are not specifically limited here.

[0127] S202: Apply the protective slurry on the surface of the second active material layer to a thickness of 10 μm to 40 μm, and after drying, obtain a protective layer. Preferably, the protective slurry is applied to a thickness of 20 μm to 30 μm.

[0128] The prepared protective slurry is applied to the surface of the second active material layer by doctor blade coating. The doctor blade thickness can be any one of 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, or 40μm, or any value in between. Limiting the doctor blade coating thickness ensures the thickness of the subsequent protective layer, preventing it from being too thick, which would increase costs and potentially reduce the thickness of the active material layer within the limited space of the battery, thereby affecting the battery's capacity. It also avoids being too thin, which would not effectively reduce the risk of thermal runaway.

[0129] Optionally, in step S202, drying is performed in a forced air drying oven at 80°C to 100°C for 8 hours to 12 hours.

[0130] [Battery]

[0131] The present invention further provides a battery, comprising: a separator, an electrolyte, and the pole piece according to any one of the above embodiments of the present invention.

[0132] If the first active material and the second active material are both positive electrode active materials, the electrode sheet is a positive electrode sheet; if the first active material and the second active material are both negative electrode active materials, the electrode sheet is a negative electrode sheet.

[0133] The battery may include only a negative electrode sheet, or only a positive electrode sheet, or both a positive electrode sheet and a negative electrode sheet.

[0134] In some embodiments, the battery further comprises a pole piece produced by the pole piece production method according to any of the above embodiments of the present invention.

[0135] The battery also includes a separator and an electrolyte. The separator can be made of any of polypropylene (PP), polyethylene (PE), polyimide (PI), or a polypropylene / polyethylene composite (PP / PE). The electrolyte's lithium salt is lithium hexafluorophosphate (LiPF6), and the solvents include cyclic carbonate (EC) and linear carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC).

[0136] Since the battery provided by the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be described in detail here.

[0137] The present application is described in detail below with reference to the following examples and comparative examples, but the implementation and protection of the present invention are not limited thereto. The following examples are only some examples of the present application and are not limitations of the present application.

[0138] 1. Preparation of positive electrode sheet

[0139] (1) Preparation of the first active material layer: The first active material includes a chemical formula of LiNi 0.8 Co 0.05 Mn 0.15 The ternary high nickel single crystal material of O2, the conductive agent and the binder are mixed evenly in a mass ratio of 97:2:1. The conductive agent is SP (conductive carbon black) and oily single-walled carbon nanotubes. The positive electrode binder is PVDF (polyvinylidene fluoride) added with NMP (N-methylpyrrolidone) and stirred into a first slurry that is mixed evenly and stable. The first slurry is evenly coated on the positive electrode current collector with a coating surface density of 155g / m 2, compacted density is 3.45g / cm 3 .

[0140] (2) Preparation of the second active material layer: The first active material includes a chemical formula of LiNi 0.8 Co 0.05 Mn 0.15 The ternary high nickel polycrystalline material, conductive agent and binder of O2 are mixed evenly in a mass ratio of 97:2:1. The conductive agent is SP (conductive carbon black) and oily single-walled carbon nanotubes. The positive electrode binder is PVDF (polyvinylidene fluoride) added with NMP (N-methylpyrrolidone) and stirred into a second slurry that is mixed evenly and stable. The second slurry is evenly coated on the above-mentioned first active material layer with a coating surface density of 155g / m 2 , compacted density is 3.45g / cm 3 .

[0141] (3) Preparation of protective layer: 100 parts by mass of silicone rubber, 45-50 parts by mass of fumed silica, 40-45 parts by mass of aluminum hydroxide, and 1.5-2 parts by mass of di-tetra-sulfurizer were stirred in a high-speed stirrer for 30 minutes to prepare a uniform slurry, which was then coated on the surface of the second active material layer with a scraper thickness of 20 μm, and then dried in an 80°C forced air drying oven for more than 8 hours.

[0142] 2. Preparation of negative electrode sheet: The active material is graphite negative electrode, the conductive agent is SP and carbon nanotubes, the adhesive is PAA (polyacrylic acid) and SBR (styrene-butadiene rubber), and the negative electrode current collector is copper foil or carbon-coated copper foil or porous copper foil. The negative electrode active material, SP, and binder are mixed in a ratio of 97:1:2, and deionized water is added and stirred to form a uniform and stable negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector with a coating surface density of 110g / m 2 After drying and cold pressing, the positive electrode sheet is obtained, and the compaction density is 1.60g / cm 3 .

[0143] 3. Isolation film: PP (polypropylene) or PE (polyethylene) is used as the isolation film base film with a thickness of 10μm.

[0144] 4. Battery cell assembly process: Arrange the positive electrode sheet, separator, negative electrode sheet and separator in sequence, and use winding as the assembly method.

[0145] 5. Preparation of electrolyte: LiPF6 was dissolved in a solvent with a volume ratio of 1:1:1 of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate, with a concentration of 1.2 mol / L.

[0146] The electrolyte was injected into the dry battery cell, soaked for 10 hours, and then formed at 45°C. The formation process was as follows: charge at 0.05C to 3.4V, and then charge at 0.2C to 3.75V; the battery was completed after aging at room temperature for 24 hours.

[0147] Example 1

[0148] In Example 1, the preparation of the positive electrode sheet, the negative electrode sheet, the isolation membrane and the electrolyte, and the assembly of the battery cell are obtained by the above method, wherein the protective layer in the positive electrode sheet includes 100 parts by mass of silicone rubber, 45 parts by mass of fumed silica, 40 parts by mass of aluminum hydroxide, and 2 parts by mass of di-tetra-sulfurizer.

[0149] Example 2

[0150] The difference of Example 2 is only that the protective layer includes 100 parts by mass of silicone rubber, 47 parts by mass of fumed silica, 40 parts by mass of aluminum hydroxide, and 2 parts by mass of bis(2,4-tetra)sulfurizer.

[0151] Example 3

[0152] The difference from Example 1 is that the protective layer comprises 100 parts by mass of silicone rubber, 50 parts by mass of fumed silica, 40 parts by mass of aluminum hydroxide, and 2 parts by mass of bis(2,4-tetra)sulfurizer.

[0153] Example 4

[0154] The difference between Example 4 and Example 1 is that the protective layer includes 100 parts by mass of silicone rubber, 50 parts by mass of fumed silica, 45 parts by mass of aluminum hydroxide, and 1.5 parts by mass of bis(2,4-tetra)sulfurizer.

[0155] Example 5

[0156] The only difference between Example 5 and Example 1 is that the thickness of the protective layer is 10 μm.

[0157] Comparative Example 1

[0158] The difference between Comparative Example 1 and Example 1 is that no protective layer is provided on the positive electrode sheet of Comparative Example 1.

[0159] Comparative Example 2

[0160] The difference between Comparative Example 1 and Example 1 is only that the amount of bis(di-tetra-sulfurized agent) is 1 part by mass.

[0161] Performance Testing

[0162] 1. Cycle test process (capacity retention after 1000 cycles): Test temperature 25°C, discharge at 1C constant current to 2.8V, let stand for 30 minutes; then charge at 1C constant current to 4.25V, discharge at constant voltage to a cutoff current of 0.05C, let stand for 30 minutes, and discharge at 1C constant current to 2.8V. The discharge capacity at this time is recorded as the initial discharge capacity. This is one charge and discharge cycle. Repeat this step until the discharge capacity is reduced to 80% of the initial discharge capacity (SOC cutoff).

[0163] 2. Flexibility test: Cut the electrode to be tested into a suitable size, generally 5 to 10 cm in length and 1 to 2 cm in width, so as to facilitate operation and observation of the winding situation. Gently pinch the other end of the electrode with your fingers and wind the electrode around the steel needle at a uniform speed. Maintain uniform force during the winding process, avoid sudden force or pauses, and try to make the electrode fit tightly on the steel needle. Start the test with a large diameter steel needle. The diameter of the steel needle ranges from 5mm to 0.1mm. When the electrode begins to crack, break or have obvious delamination, the steel needle one size larger than this diameter is the verified diameter. The diameter of the steel needle indicates its flexibility.

[0164] 3. Working temperature range test: According to the test requirements, set the target temperature of the high and low temperature box. When the high and low temperature box reaches the target temperature, put the sample (the positive electrode prepared in the embodiment or comparative example) in. The test time is 2 to 4 hours. After the specified test time is reached, take out the sample and cool it to room temperature. Then observe the changes in the appearance of the sample, such as whether there is discoloration, cracks, blistering, degumming, etc. And there is no cracking of the electrode. Test until the upper failure phenomenon occurs, which is the boundary temperature of the protective layer. The test temperature is from -40 to 220 ° C, and the interval of 10 ° C is a test point. The test points are all independently tested with new electrodes.

[0165] The test results of the above performance test are shown in Table 1.

[0166] Table 1. Test results:

[0167]

[0168] As can be seen from Table 1, compared to Comparative Examples 1-2, the protective coatings (protective layers) of Examples 1-5 help reduce side reactions between the electrode and the electrolyte, improving the electrode's cycling performance. The flame-retardant silicone rubber, with its excellent thermal insulation, reduces the effects of heat diffusion on the electrode, improving battery safety. Furthermore, the electrode's operating temperature range is increased. Furthermore, the addition of the coating improves the electrode's flexibility and reduces damage to the electrode during processing.

[0169] In Comparative Example 1, the cycle performance is reduced without adding a protective coating. In Comparative Example 1, the mechanical strength and aging resistance of the protective coating with less cross-linking agent are reduced, resulting in failure of the protective coating. The protective effect decreases as the cycle progresses. In Comparative Example 1, the first active material and the second active material of the positive electrode plate have failed at above 130°C.

[0170] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0171] The basic principles of the present invention have been described above in conjunction with specific embodiments. However, it should be noted that the advantages, strengths, and effects mentioned in the present invention are merely illustrative and non-limiting, and should not be construed as necessarily possessed by each embodiment of the present invention. Furthermore, the specific details disclosed above are provided for illustrative purposes and to facilitate understanding, and are not intended to be limiting. These details do not necessarily limit the present invention to being implemented using these specific details.

[0172] It should be noted that the terms "and / or" or " / " used herein are merely a description of an association relationship between associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone. The singular forms "a," "the," and "the" used in the embodiments of the present invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0173] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0174] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A pole piece, characterized in that: include: current collector; a first active material layer, the first active material layer being disposed on at least one surface of the current collector, the first active material layer comprising a first active material; a second active material layer, the second active material layer being disposed on a surface of the first active material layer away from the current collector, the second active material layer comprising a second active material; A protective layer is provided on a surface of the second active material layer away from the first active material layer, and the protective layer comprises silicone rubber and additives.

2. The pole piece according to claim 1, characterized in that: The protective layer comprises the following components in parts by mass: 100 parts of silicone rubber and 86.5-97 parts of additives; Preferably, the additives include a flame retardant, a reinforcing agent and a vulcanizing agent, and the masses of the flame retardant, the reinforcing agent and the vulcanizing agent are not 0; Preferably, the protective layer comprises the following components in parts by mass: 100 parts of silicone rubber, 45-50 parts of reinforcing agent, 40-45 parts of flame retardant and 1.5-2 parts of vulcanizing agent.

3. The pole piece according to claim 2, characterized in that: The protective layer satisfies at least one of the characteristics (1) to (3): (1) The flame retardant includes at least one of aluminum hydroxide and magnesium hydroxide; (2) The reinforcing agent includes fumed silica; (3) The vulcanizing agent includes a di-tetra-sulfurizing agent.

4. The pole piece according to claim 1, characterized in that: The first active material and the second active material are positive electrode active materials, and the electrode sheet satisfies at least one of the characteristics (1) to (3): (1) The first active material includes ternary material A; Preferably, the ternary material A comprises LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein, x ≥ 0.8, 0.05 ≤ y ≤ 0.2; Preferably, the ternary material A comprises primary particles; (2) the second active material includes ternary material B; Preferably, the ternary material B comprises LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein, x ≥ 0.8, 0.05 ≤ y ≤ 0.2; Preferably, the ternary material B includes secondary particles; (3) Both the first active material and the second active material contain nickel, and the nickel content in the first active material is different from the nickel content in the second active material.

5. The pole piece according to claim 1, characterized in that: The first active material and the second active material are negative electrode active materials, and the electrode sheet satisfies at least one of the characteristics (1) to (4): (1) The first active material includes at least one of a silicon-based material and a carbon-based material; (2) the first active substance includes primary particles; (3) the second active material includes at least one of a silicon-based material and a carbon-based material; (4) The second active material includes secondary particles.

6. The pole piece according to claim 1, characterized in that: The thickness of the protective layer is 3 μm to 10 μm; And / or, the surface density of the protective layer is 15 mg / m 2 ~30 mg / m 2 .

7. The pole piece according to any one of claims 1 to 6, characterized in that: The electrode meets at least one of the characteristics (1) to (4): (1) Based on the mass of the first active material layer, the mass proportion of the first active material is 95% to 97%; (2) The first active material layer further includes a first conductive agent and a first binder; Preferably, based on the mass of the first active material layer, the mass proportion of the first conductive agent is 1% to 1.5%; Preferably, based on the mass of the first active material layer, the mass proportion of the first binder is 2% to 3.5%; Preferably, the first conductive agent comprises one or more of conductive carbon black, vapor-generated carbon fibers, graphene, or carbon nanotubes; (3) Based on the mass of the second active material layer, the mass proportion of the second active material is 95% to 97%; (4) The second active material layer further includes a second conductive agent and a second binder; Preferably, based on the mass of the second active material layer, the mass proportion of the second conductive agent is 1% to 1.5%; Preferably, based on the mass of the second active material layer, the mass proportion of the second binder is 2% to 3.5%; Preferably, the second conductive agent includes one or more of conductive carbon black, vapor-generated carbon fibers, graphene or carbon nanotubes.

8. A method for preparing a pole piece, characterized in that: The following steps are involved: Coating a first slurry on at least one side of the current collector to obtain a first active material layer; coating a second slurry on the surface of the first active material layer to obtain a second active material layer; coating a protective slurry on the surface of the second active material layer to obtain a protective layer; The first active material layer includes a first active material; the second active material layer includes a second active material; and the protective layer includes silicone rubber and additives.

9. The preparation method according to claim 8, characterized in that The step of obtaining the protective layer specifically includes: The silicone rubber and the additive are mixed evenly to obtain a protective slurry; preferably, the silicone rubber, the flame retardant, the reinforcing agent and the vulcanizing agent are mixed evenly to obtain a protective slurry; The protective slurry is coated on the surface of the second active material layer with a doctor blade having a coating thickness of 10 μm to 40 μm. After drying, the protective layer is obtained.

10. A battery, characterized in that: include: A diaphragm, an electrolyte, and a pole piece according to any one of claims 1 to 7, and / or a pole piece prepared by the preparation method according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Pole piece, preparation method of pole piece and battery

    CN111916645A

  • Secondary battery and electric device

    CN116314800A

  • Pole piece for battery, preparation method of pole piece, battery and electric equipment

    CN116705982A

  • Pole piece and preparation method thereof, battery cell and lithium ion battery

    CN116741932A

  • Positive plate, preparation method thereof and battery

    CN118448569A